Next Generation Bone Marrow Adiposity Researchers: Report From the 1st BMAS Summer School 2021 - Labella, Rossella; Little-Letsinger, Sarah; Avilkina, Viktorjia; Sarkis, Rita; Tencerova, Michaela; Vlug, Annegreet; Palmisano, Biagio (Frontiers in Endocrinology, 2022)
The first International Summer School on Bone Marrow Adiposity was organized by members of Bone Marrow Adiposity Society and held virtually on September 6-8 2021. The goal of this meeting was to bring together young scientists interested in learning about bone marrow adipose tissue biology and pathology. Fifty-two researchers from different backgrounds and fields, ranging from bone physiopathology to adipose tissue biology and hematology, participated in the summer school. The meeting featured three keynote lectures on the fundamentals of bone marrow adiposity, three scientific workshops on technical considerations in studying bone marrow adiposity, and six motivational and career development lectures, spanning from scientific writing to academic career progression. Moreover, twenty-one participants presented their work in the form of posters. In this report we highlight key moments and lessons learned from the event.